Fictions of law and custom: passing narratives at the fins des siècles - Moynihan, Sinéad (2007)
This dissertation examines narratives of passing of the nineteenth- and twentieth century fins de siècle. My central thesis is that passing narratives of the 1990s and beyond evidence symmetry between the tropes of passing that occur at plot level and passing strategies surrounding the production of the texts themselves. I argue that the connections between passing and authorship that emerge in contemporary stories invite us to reconsider extant interpretations of earlier passing stories, specifically those published at the turn of the twentieth century. The Introduction challenges the historiography of the passing narrative traced in existing studies of passing. It also suggests the ways in which authorship and passing are inextricably linked via the arbitrary standard of "authenticity," both authorial and racial. In Chapter One, I examine the relationship between the African American body-as-text and the African American author who produces a text in The Bondwoman's Narrative (date unknown), Philip Roth's The Human Stain (2000) and Percival Everett's Erasure (2001). Chapter Two takes the self-reflexive detective genre and traces the changing roles of the passing character within the conventions of the form, from femme fatale to hard-boiled detective. Here, I focus specifically on Pauline Hopkins's Hagar's Daughter (1901-1902), Walter Mosley's Devil in a Blue Dress (1990) and Robert Skinner's Wesley Farrell series (1997-2002). In Chapter Three, I examine texts whose protagonists' gender and/or racial ambiguity serve to destabilise analogously the religious categories under interrogation in those texts, namely Hopkins's Winona (1902) and Louise Erdrich's Tracks (1988) and The Last Report on the Miracles at Little No Horse (2001). Chapter Four examines tropes of passing in relation to three contemporary novels of adolescence, Paul Beatty's The White Boy Shuffle (1996), Danzy Senna's Caucasia (1998) and Jeffrey Eugenides's Middlesex (2002). Finally, the Conclusion discusses recent controversies of authorship and authenticity in the U.S., particularly as these pertain to the ambiguous literary category of "memoir."